Thermo-mechanical behaviour of ultra-high strength concrete encased steel columns in standard fires. (15th March 2021) - Du, Yong; Qi, Hong-hui; Jiang, Jian; Richard Liew, J.Y.; Li, Shan
Highlights: Transient thermal strain is considered in the model of ultra-high strength concrete encased steel columns (UHSCESC). Steel section has a lower temperature than its critical value after 150 min's heating in standard fire. The fire behavior of UHSCESC is governed evenly by steel section and core concrete. The slenderness ratio, section size and load ratio are three key influencing factors. EC4 is not applicable to UHSCESC leading to unconservative fire resistances up to 66 min. Abstract: Ultra-high strength concrete has been applied in concrete encased steel column to enhance strength and reduce usage of concrete. However, there are limited specifications in current design codes on ultra-high strength concrete encased steel columns (UHSCESC), particularly for fire effects. This paper presents numerical simulation of fire behaviour of UHSCESC exposed to standard fires. A thermo-mechanical model of UHSCESC is established by considering the effect of transient thermal strain and validated against experimental results. The effect of slenderness ratio, section size, load ratio, concrete strength, steel strength, reinforcement ratio and steel ratio on the fire behaviour of UHSCESC is investigated through parametric studies. The predicted fire resistance of UHSCESC is finally compared to EC4 results. It is found that the temperature of the steel section is lower than its critical value, and the load bearing capacity of UHSCESC is almost evenly provided by the core concrete and steel section. The slenderness, section size and load ratio have significant effects on fire resistance of UHSCESC, leading to a wide range more than 300 min. The EC4 method is not applicable to UHSCESC which may provide unconservative fire resistances up to one hour and over-conservative results of nearly four hours.